Chitosan modified epat full biodegradable edible fungus cultivation bag composite material and preparation process thereof

CN122876751APending Publication Date: 2026-10-09黄宇翀 +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611098105.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

传统聚丙烯塑料袋不可生物降解,废弃后造成白色污染;现有全生物降解膜大多采用 PLA/PBAT 共混体系,存在显著短板: 1、高温高压蒸汽灭菌工况下,薄膜力学性能大幅衰减,极易出现软化、穿孔、分层,造成菌棒报废; 2、普通降解膜不具备长效抗菌能力,栽培阶段木霉、青霉、毛霉滋生引发绿霉污染,生产损耗高; 3、材料降解时序不可控:部分薄膜养菌阶段(120 天密闭高湿培养)提前粉化破损,无法支撑完整出菇周期;部分薄膜堆肥环境下降解缓慢,难以满足欧盟 EN13432 可堆肥标准

Benefits of technology

[0014]1、本发明以 EPAT 为唯一主体基体树脂,搭配季铵化壳聚糖微球改性体系,三层功能分层设计,能够承受 110~120℃高压蒸汽灭菌,灭菌后力学强度保留率≥85%,解决常规 PLA/PBAT 膜高温破损难题; 2、定向抑制木霉、青霉、毛霉等食用菌主要杂菌,大幅降低菌棒绿霉污染报废率; 3、实现时序可控降解:养菌周期维持膜体完整,废弃后可完全生物降解,兼顾生产使用需求与环保政策要求; 4、壳聚糖组分被稳定锁合在基体内部,高湿条件下迁移量低,满足欧盟食品接触安全标准,具备国内与海外食用菌基地出口应用潜力;5、材料经堆肥降解后生态毒性符合 EN13432 要求,堆肥种植小麦、绿豆的发芽率与生物量相对于空白堆肥均大于 90%,且 SVHC、重金属、邻苯类、PCP、农药残留等有害物质均未检出,符合欧盟 REACH 及食品接触材料法规要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122876751A_ABST
    Figure CN122876751A_ABST
Patent Text Reader

Abstract

The application discloses a chitosan modified EPAT full-biodegradable edible mushroom cultivation bag composite material and a process. The material adopts a three-layer co-extrusion structure, the inner layer contains quaternary ammonium chitosan microspheres, a compatibilizer and a chain extender, the core layer contains organic intercalation nano fillers, and the outer layer contains a bio-based weather-resistant stabilizer; the three-layer structure is all taken as a continuous phase of EPAT, and no PLA, PBAT and PGA main body blending components are introduced. After the material is sterilized at 120-125 DEG C and 0.12-0.14 MPa for 30 min, the longitudinal and transverse strength retention rate is greater than or equal to 85%, the 24h antibacterial rate on Trichoderma and other strains is greater than or equal to 95%; under the condition of 20-25 DEG C and relative humidity greater than or equal to 80%, the degradation induction period is greater than or equal to 120 days, the industrial composting 171d biodegradation rate is greater than or equal to 85%, the relative biodegradation rate is greater than or equal to 90%, the composting germination rate and biomass are greater than or equal to 90%, and the material is suitable for long-period industrial cultivation of edible mushrooms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fully biodegradable polymer composite materials technology, specifically relating to a chitosan-modified EPAT multilayer co-extruded composite material, which is particularly suitable for industrialized edible mushroom cultivation bags and has the characteristics of high temperature and high pressure sterilization resistance, long-lasting antibacterial effect, and controllable induced time-sequential degradation. Background Technology

[0002] In the industrialized cultivation of edible fungi, the substrate spawn needs to be sterilized by high-pressure steam at 110℃~120℃ to kill miscellaneous bacteria in the culture medium. Traditional polypropylene plastic bags are non-biodegradable and cause white pollution after disposal. Most existing fully biodegradable films use a PLA / PBAT blend system, which has significant shortcomings: 1. Under high-temperature and high-pressure steam sterilization, the mechanical properties of the film are greatly reduced, making it prone to softening, perforation, and delamination, resulting in the scrapping of the substrate spawn; 2. Ordinary biodegradable films do not have long-term antibacterial ability, and the growth of Trichoderma, Penicillium, and Mucor during the cultivation stage causes green mold contamination, resulting in high production losses; 3. The degradation sequence of the material is uncontrollable: some films prematurely pulverize and break during the mycelium cultivation stage (120 days of closed high-humidity cultivation), unable to support a complete fruiting cycle; some films degrade slowly under composting conditions, making it difficult to meet the EU EN13432 compostability standard.

[0003] Chitosan is a natural biodegradable antibacterial material, but it is highly polar and has poor compatibility with hydrophobic polyesters such as PLA and PBAT. Direct blending can easily lead to agglomeration. Under high humidity sterilization conditions, the active components are prone to migration and precipitation, making it difficult to apply to edible fungi cultivation.

[0004] EPAT, as a novel fully biodegradable polyester, has excellent resistance to damp heat, but pure EPAT film has insufficient antibacterial ability and limited water vapor barrier performance, which limits its promotion in the field of edible fungus cultivation bags.

[0005] Therefore, the industry urgently needs a special composite material that simultaneously meets the following requirements: resistance to high-temperature sterilization, long-term inhibition of miscellaneous bacteria in edible fungi, stable structure during the culture cycle, complete biodegradability after disposal, and low material migration. Summary of the Invention

[0006] Purpose of the invention

[0007] To overcome the shortcomings of existing PLA / PBAT degradable films, such as poor high-temperature resistance, short antibacterial effect, and unbalanced degradation sequence, a chitosan-modified EPAT three-layer co-extruded composite material is provided, which is suitable for high-pressure sterilization and long-cycle cultivation of edible fungi. Technical solution

[0008] A chitosan-modified EPAT fully biodegradable edible mushroom cultivation bag composite material is produced by three-layer co-extrusion molding. From the inside out, it consists of an antibacterial and biodegradable inner layer, a high-barrier water-retaining core layer, and a moisture- and heat-resistant anti-aging outer layer. All three layers use EPAT biodegradable polyester as the continuous phase matrix resin, without introducing PLA, PBAT, PGA, or other similar components as main blending elements. The antibacterial and biodegradable inner layer contains quaternized chitosan microspheres, reactive compatibilizers, and chain extenders. The high-barrier water-retaining core layer contains organically intercalated layered nanofillers. The moisture- and heat-resistant anti-aging outer layer contains bio-based weather stabilizers. The composite material meets the following performance indicators: (1) After sterilization with high-pressure steam at 110℃~120℃ and 0.12~0.14MPa for 30min (mechanical properties are tested according to GB / T 1040.3), the retention rate of longitudinal and transverse tensile strength of the film is ≥85%, and the film is free of pinholes, perforations, delamination and peeling; (2) The film has an antibacterial rate of ≥95% against Trichoderma, Penicillium and Mucor for 24h (tested according to GB / T 21510-2008); (3) Under closed dark culture conditions at 20~25℃ and relative humidity ≥80%, the degradation induction period is ≥120 days; the biodegradation rate in the composting environment is ≥85% after 171d (measured according to EN13432), meeting the compostability standard; (4) Under high humidity sterilization and cultivation conditions, the migration of active components meets the EU 10 / 2011 food contact material limit requirements (refer to (EU) No 10 / 2011). (Appendix: Migration Test Method), and complies with (EU) No 1935 / 2004 General Safety Requirements for Food Contact Materials.

[0009] The antibacterial and stable degradation inner layer is enriched with quaternized chitosan microspheres. When the relative humidity of the environment is ≥60%, the chitosan microspheres are enriched with microorganisms, which induces the hydrolysis of polyester ester bonds. The degradation rate of the inner layer is 1.5 to 3 times higher than that of the moisture-resistant and heat-resistant anti-aging outer layer, thus achieving time-differentiated degradation.

[0010] Preferably, the thickness ratio of the three layers is: inner layer 15%–25%, core layer 50%–70%, and outer layer 15%–25%. Preferably, the quaternized chitosan microspheres have a particle size of 0.5–5 μm and a degree of quaternization substitution of 0.3–0.6. Explanation of the collaborative mechanism

[0011] This invention employs a three-layer functionalized structure design to lock quaternized chitosan microspheres within the inner continuous phase. During sterilization and high-humidity cultivation, the interfacial covalent bonds formed by reactive compatibilizers and chain extenders significantly inhibit chitosan migration to the membrane surface. Simultaneously, under high-humidity conditions, chitosan microspheres accumulate on the inner surface, selectively catalyzing ester bond hydrolysis and inducing preferential degradation of the inner layer. Meanwhile, the outer layer's degradation is delayed due to the protection of the moisture- and heat-resistant anti-aging system, thus achieving a dual balance of "structural stability during the cultivation period and time-controlled degradation after disposal."

[0012] This invention also provides a preparation process for the above-mentioned composite material, comprising the following steps: S1, Masterbatch preparation: Inner layer masterbatch, core layer masterbatch, and outer layer masterbatch are prepared separately; each component is fed into a twin-screw extruder, and segmented temperature-controlled melt extrusion, vacuum devolatilization, water-cooled pelletizing, and drying are performed for later use; S2, Three-layer co-extrusion molding: The three masterbatches are fed into a three-layer co-extrusion extruder unit, the melt is combined through a distributor, and the die head is used for integrated co-extrusion to form a three-layer composite film; S3, Traction, shaping, and winding: The target composite film is obtained.

[0013] Preferably, the temperature control range of each section of the twin-screw extruder is 160℃~210℃; the co-extrusion die temperature is 165~205℃; and a multi-stage vacuum devolatilization device is set throughout the process to reduce the risk of small molecule precipitation. Beneficial effects

[0014] 1. This invention uses EPAT as the sole main matrix resin, combined with a quaternized chitosan microsphere modification system, featuring a three-layer functional design. It can withstand high-pressure steam sterilization at 110–120℃, retaining ≥85% of its mechanical strength after sterilization, thus solving the problem of high-temperature damage in conventional PLA / PBAT membranes. 2. It directionally inhibits major contaminating fungi in edible fungi, such as Trichoderma, Penicillium, and Mucor, significantly reducing the rate of mold contamination and waste in mushroom substrate. 3. It achieves time-controlled degradation: the membrane maintains integrity throughout the cultivation cycle and is completely biodegradable after disposal, balancing production needs with environmental policy requirements. 4. The chitosan component is stably locked within the matrix, exhibiting low migration under high humidity conditions, meeting EU food contact safety standards, and possessing export application potential for domestic and overseas edible fungi bases. 5. The ecotoxicity of the material after composting degradation complies with EN13432. The requirements are that the germination rate and biomass of wheat and mung beans grown in compost are both greater than 90% compared to the blank compost, and no harmful substances such as SVHC, heavy metals, phthalates, PCP, and pesticide residues are detected, which complies with the EU REACH and food contact material regulations. Attached Figure Description

[0015] Figure 1 is a schematic cross-sectional view of the three-layer composite structure of the present invention; 1 - antibacterial and biodegradable inner layer, 2 - high-barrier water-retaining core layer, 3 - moisture- and heat-resistant and anti-aging outer layer; Abstract: Figure 1 is selected as the accompanying drawing. Detailed Implementation

[0016] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to the following embodiments. Example 1

[0017] The thickness ratio of the three layers is as follows: inner layer 20%, core layer 60%, outer layer 20%; Inner layer masterbatch: EPAT + quaternized chitosan microspheres (particle size 2μm, degree of substitution 0.45) + reactive compatibilizer + chain extender; Core layer masterbatch: EPAT + organic intercalated montmorillonite nanofiller; Outer layer masterbatch: EPAT + bio-based weather stabilizer; The masterbatch preparation and three-layer co-extrusion film are completed according to the above process.

[0018] Explanation of the identity between the sample and the testing system: The EPAT matrix resin and quaternized chitosan microsphere modification system used in this embodiment are identical to the samples involved in the following third-party testing report in terms of formulation principle, matrix type, and modification mechanism: “EPAT Biodegradable Plastics” (Micro-Spectrum Report WP-21077847-JC-01); “EPAT Chitosan Degradable Bag” (Guangwei Test Report 2022ESQ00337R02, Micro-Spectrum Report WP-22037953-JC-02CnR1); "Disposable biodegradable food box" (SGS reports CANEC23015233602, CANEC23015233604, CANEC23015289204). Although the above samples have different uses or forms, they are all prepared based on the same EPAT matrix and chitosan modification route. Their degradation behavior, ecological safety, and material migration characteristics can represent the performance of the composite material of this invention under the same environment.

[0019] Performance test data: After sterilization with steam at 115℃ and 0.13MPa for 30 minutes, the sample retained 87.2% of its longitudinal and transverse tensile strength, and the film remained intact without damage; the inhibition rate against Penicillium and Trichoderma was 96.1% after 24 hours; after 120 days of closed cultivation at 23℃ and 82% humidity, the film did not show large-scale powdering; under industrial composting conditions, the biodegradation rate was 89.3% after 171 days, with a relative biodegradation rate of 91.2%, meeting the requirements of EN13432; compost ecotoxicity tests showed that the germination rate and biomass of wheat and mung beans planted in the compost were ≥90% compared to the blank compost, meeting the requirements of EN13432 Annex A.4; the results of substance migration and hazardous substance detection showed that Cd, Pb, Hg, Cr(VI), PBBs, PBDEs, phthalates (DBP, BBP, DEHP, DIBP), and SVHCs (ECHA 235 published as of June 14, 2023) were negative. All candidate substances and potential SVHCs were below the reporting limit (ND). Pentachlorophenol (PCP), arsenic, and various pesticide residues were not detected, which complies with the requirements of EU 10 / 2011, (EU) No 1935 / 2004, and REACH regulations. The degradation rate of the inner layer was 2.1 times that of the outer layer, showing obvious time-differentiated degradation characteristics. Comparative Example 1 (Traditional PLA / PBAT blended monolayer degradable membrane)

[0020] Commercially available PLA / PBAT biodegradable films, without the addition of a chitosan antibacterial system, showed severe embrittlement after autoclaving at 115°C for 30 minutes. The tensile strength retention rate was only 41%, and pinholes appeared in multiple locations. The films lacked specific inhibitory capabilities against other microorganisms, and surface powdering occurred after 92 days of closed-system incubation. This indicates that the PLA / PBAT system cannot meet the mechanical performance requirements under the autoclaving conditions for edible fungi. Comparative Example 2 (Pure EPAT monolayer film)

[0021] The EPAT system lacks chitosan modification and a three-layer structure; its mechanical properties after sterilization are acceptable, but it lacks long-lasting antibacterial effects and cannot achieve differentiated time-sequential degradation. This indicates that the single EPAT system lacks the ability to provide long-lasting antibacterial effects and regulate degradation time, making it unsuitable for the needs of long-cycle edible fungi cultivation.

Claims

1. A chitosan-modified EPAT fully biodegradable edible mushroom cultivation bag composite material, characterized in that, It adopts a three-layer co-extrusion molding process, consisting of an antibacterial and biodegradable inner layer, a high-barrier water-retaining core layer, and a moisture- and heat-resistant and anti-aging outer layer from the inside out. All three layers use EPAT biodegradable polyester as the continuous phase matrix resin, without introducing PLA, PBAT, or PGA as the main blending components; The antibacterial and biodegradable inner layer comprises quaternized chitosan microspheres, reactive compatibilizers, and chain extenders. The high-barrier water-retaining core layer contains organic intercalated layered nanofillers; The moisture- and heat-resistant, anti-aging outer layer contains a bio-based weather stabilizer. After being sterilized by high-pressure steam at 110℃~120℃ and 0.12~0.14MPa for 30 minutes, the composite material retains ≥85% of its longitudinal and transverse tensile strength, and the membrane is free of pinholes, perforations, and delamination; it exhibits ≥95% inhibition rate against Trichoderma, Penicillium, and Mucor over 24 hours; its degradation induction period is ≥120 days under closed dark culture conditions at 20~25℃ and relative humidity ≥80%; and its biodegradation rate is ≥85% and relative biodegradation rate is ≥90% under industrial composting conditions over 171 days.

2. A preparation process for the chitosan-modified EPAT fully biodegradable edible mushroom cultivation bag composite material as described in claim 1, characterized in that, Includes the following steps: S1. Masterbatch preparation: Prepare inner layer masterbatch, core layer masterbatch and outer layer masterbatch separately. Put each component into a twin-screw extruder, perform segmented temperature-controlled melt extrusion, vacuum devolatilization, water-cooled pelletizing and drying for later use. S2, Three-layer co-extrusion molding: Three masterbatches are fed into the three-layer co-extrusion extruder unit, the melt is combined by the distributor, and the die head is used to co-extrude to form a three-layer composite film. S3. Traction, shaping, and winding are performed to obtain the target composite material film. The twin-screw extruder has a temperature range of 160℃ to 210℃ in each section and a co-extrusion die temperature range of 165℃ to 205℃. It is equipped with a multi-stage vacuum devolatilization device throughout the process.

3. The composite material according to claim 1, characterized in that, The thickness ratio of the three layers is as follows: inner layer 15%–25%, core layer 50%–70%, and outer layer 15%–25%.

4. The composite material according to claim 1, characterized in that, The quaternized chitosan microspheres have a particle size of 0.5 μm to 5 μm and a degree of quaternization of 0.3 to 0.

6.

5. The composite material according to claim 1, characterized in that, The antibacterial and degradable inner layer is enriched with quaternized chitosan microspheres. When the relative humidity of the environment is ≥60%, the chitosan microspheres induce the hydrolysis of polyester ester bonds, and the degradation rate of the inner layer is 1.5 to 3 times higher than that of the moisture-resistant and heat-resistant anti-aging outer layer, thus achieving time-differentiated degradation.

6. The composite material according to claim 1, characterized in that, The ecotoxicity of the composite material after composting and degradation meets the requirements of EN13432; under composting conditions, the germination rate of wheat and mung bean seeds and the biomass of the plants are both ≥90% compared with the blank composting group.

7. The composite material according to claim 1, characterized in that, The content of cadmium, lead, mercury, hexavalent chromium, polybrominated biphenyls, polybrominated diphenyl ethers, phthalates, and substances on the REACH SVHC candidate list in the composite material is below the detection limit; the material meets the safety specifications for food contact materials of (EU) No 10 / 2011 and (EU) No 1935 / 2004.

8. The preparation process according to claim 2, characterized in that: The inner layer masterbatch is composed of EPAT, quaternized chitosan microspheres, reactive compatibilizers, and chain extenders; the core layer masterbatch is composed of EPAT and organic intercalated montmorillonite; and the outer layer masterbatch is composed of EPAT and bio-based weather stabilizers.

9. The preparation process according to claim 2, characterized in that, The reactive compatibilizer is an interfacial compatibilizer containing epoxy functional groups or isocyanate functional groups, and the chain extender is selected from multifunctional epoxy chain extenders.

10. The preparation process according to claim 2, characterized in that, The working vacuum degree of the multi-stage vacuum devouring device is not lower than -0.08 MPa.